By the Honorable Jonathan Trumbull, Esq ; governor of the English colony of Connecticut ... A proclamation : ... Thursday, the twenty-third day of November next, to be observed as a day of public thanksgiving ... Given under my hand in the Council chamber in New-Haven, the 30th day of October ... 1769 ([Printed by Green and Watson], 1769)
October 30, 1769 broadside issued by Governor Jonathan Trumbull of Connecticut, proclaiming November 23rd as a day of public thanksgiving for the plentiful harvest and continued good relations with the king.